THE EFFECT OF BENSON RELAXATION ON PAIN LEVELS IN BREAST CANCER PATIENTS AT EDUARDO XIMENES GENERAL HOSPITAL, BAUCAU, TIMOR-LESTE - Solangia Cabral Da Conceicao Santos; Ketut Lisnawati; Theresia Anita Pramesti (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Pain in breast cancer is one of the most common and significant problems experienced by patients. If not properly managed, the impact of breast cancer pain can lead to increased morbidity and a diminished quality of life. This study aims to determine the effect of Benson relaxation on pain levels in breast cancer patients. A quantitative research method was employed using a pre-experimental one-group pre-test and post-test design. The sample consisted of 17 patients selected through purposive sampling. Data were collected using the Numeric Rating Scale (NRS). The average pain score of respondents during the first measurement (pre-test) was 6.12, and during the second measurement (post-test) it decreased to 3.12. The difference in average pain levels between the first and second measurements showed a reduction of 3.00 points. The statistical test results revealed an Asymp. Sig (2-tailed) p-value of 0.000, indicating a significant effect of Benson relaxation on reducing pain in breast cancer patients. Benson relaxation can significantly help lower pain levels after therapy. This relaxation technique plays an important role by inhibiting sympathetic nerve activity, which in turn reduces oxygen consumption by the body and relaxes the muscles, leading to a sense of calm and comfort.